Understanding the factors affecting attrition and intention to leave of health extension workers: a mixed methods study in Ethiopia - Merhawi Gebremedhin Tekle; Habtamu Milkias Wolde; Girmay Medhin; Alula M. Teklu; Yibeltal Kiflie Alemayehu; Esie Gebrewahd Gebre; Frehiwot Bekele; Nikita Arora (BMC, 2022)
Abstract Background The Health Extension Program (HEP) is Ethiopia's flagship community health program, launched in 2003. Health Extension Workers (HEWs) are key vehicles for the delivery of the HEP. While it is believed that there is high attrition among HEWs, the magnitude of or reasons for attrition is unknown. Their intention to leave their jobs in the next 5 years has also never been investigated on a national scale. This study aimed to assess the magnitude of, and factors affecting HEWs' attrition and intention to leave in Ethiopia. Methods The study used mixed methods to address the research objectives. Using stratified random sampling and regions as strata, 85 districts from nine regions were randomly selected in Ethiopia. Within each study district, six kebeles (village clusters) were randomly selected, and all HEWs working in these kebeles were interviewed to capture their 5-year intention to leave. The study team developed a data-extraction tool for a rapid review of district-level documents covering the period June 30, 2004 through June 30, 2019 to gather their attrition figures. We used survival analysis to model attrition data and checked model goodness-of-fit using the Cox-Snell residual test. We additionally collected qualitative data from HEWs who had left their positions. Results The attrition of HEWS over the lifespan of the HEP was 21.1% (95% CI 17.5-25.3%), and the median time to exit from HEWs workforce was 5.8 years. The incidence rate was 3.1% [95% CI 2.8-3.4]. The risk of attrition was lower amongst HEWs with level four certifications, with children, and among those working in urban settings. By contrast, HEWs who were not certified with a certificate of competency (COC), who were deployed after 2008, and those who were diploma/degree holders were more likely to exit the HEWs workforce. The magnitude of intention to leave was 39.5% (95% CI 32.5-47%) and the primary reasons to leave were low incentives, dearth of career development opportunities (50.8%), high workload (24.2%), and other psychosocial factors (25%). Conclusion Although the magnitude of attrition is not worryingly high, we see high magnitude in HEWs' intention to leave, indicating a dissatisfied workforce. Multiple factors have contributed to attrition and intention to leave, the prevalence of many of which can be reduced to fit the needs of this workforce and to retain them for the sustained delivery of primary healthcare in the country. Ensuring HEWs' job satisfaction is important and linked with their career development and potentially higher rates of retention.